PENGARUH MUSIK SIHUTUR SANGGUL PADA PENCIPTAAN TARI KREASI DAERAH BATAK TOBA DI KOTA MEDAN - DESI PURNAMA SARI (Universitas Negeri Medan, 2013)
The Influence Of Sihutur On The Creation Of Bun Music Dance Creations The Batak Toba In Medan The purpose of this research is to discuss about the Toba Batak music arrangement Sihutur Bun which is a trend among artists of dance are used as accompaniment in music creation dance creations area as a result of the creativity of artists dance in dance class Nusindo, SMK Raksana 2, Prodi Dance UNIMED and Siti Hajar's Education Foundation. To discuss this research uses theories that relate to such topics as understanding the science of influence, sets the dance (choreography) and creativity in the creation of dance. The method used is the method of qualitative, with a population of deskriftif at the same time as the sample of interviewees, composer, choreographer. Data collection techniques include the study of librarianship, observation, interview and documentation. The results of this research are: i. Sihutur Bun created musical arrangements Hendry Perangin Wind is divided into 3 parts namely: part 1. As a carrier of melody is a musical instrument Taganing, part 2. Sulim and Hasapi instruments for melodies, part 3. Sarune Bolon instrument, used as a carrier of melody. The musical arrangement was later utilized by individual choreographers to create works in accordance with his creativity, arranged by: 1. contents, 2. the plots of arable Form, and 3. The technique, which is performed with improvisation, exploration and forming. The influence of Sihutur Bun music inspired to dance artists in creating new dance creations. II. the creativity of each choreographer me Keywords: music